(untitled) (Revista científica Olimpia, 2019)
The World Health Organization predicts that between 2000 and 2050, the proportion of people over the age of 60 will double. In this order reaching the elderly with quality of life continues to constitute an aspiration of humanity, being also an indicator of development and good health; however, achieving this is a challenge, not only medically, but also personal, social and political; that is why keeping a passive look at this reality can become a serious problem for society. In correspondence with the above and considering the importance of the practice of recreational recreational activities in its various manifestations and population groups the work presented has the objective: To determine the incidence of activities in the maintenance of the functional independence of the Elderly Of the Center "San Ignacio de Loyola. Based on a mixed research methodology, with the use of quantitative and qualitative methods and the use of instruments such as the observation guide and the Katz test, the research hypothesis is contrasted, with the interpretation that the playful activities positively favored functionality in the basic activities of the daily life of participating older adults. All of which was proven by applying the correlational statistic with the Wilcoxon segment range test. Finally, the overall contrast of values led to the conclusion that the participating older adults had statistically significant differences in their levels of functional independence.